Building the Entrepreneurial Spirit of Students: The Case of an Islamic Boarding School - Ali Idrus; Sukandar Hadi (Universitas Jambi, Indonesia, 2022)
This research aimed to analyse the entrepreneurial spirit of students in Islamic boarding schools. It used a qualitative approach. This research was conducted in Nurul Iman Islamic boarding school students. The data were obtained through observation and interviews. The data analysis techniques used were data collection, reduction, data presentation, verification, and conclusion. Researchers' findings and analyses led them to the conclusion that the implementation of the program to develop the entrepreneurial spirit of students at the Islamic boarding school applies life skills education ranging from hard skills to foster the independence of students in developing an entrepreneurial spirit.